THE MEDIATING EFFECT OF INTEREST ON THE RELATIONSHIP BETWEEN DEMORAPHIC ASPECTS AND THE DECISION FOR BEING AND ENTREPRENEUR - Hendrawijaya, Arief Tukiman (Review of Management and Entrepreneurship, 2019)
The study analyzes the effect of age, education, gender, experience, and the number of family members on the interest to be an entrepreneur and entrepreneurial decision. In addition, the study tests whether the interest to be an entrepreneur mediates the effect of age, education, gender, experience, and family number on the decision to be an entrepreneur. The population of the study are the street vendors in the Jember downtown. The samples consist of 192 respondents. This research uses the path analysis to determine the direct and indirect effects. The results show that age, education, gender, experience, and the number of family member have positive and significant effects on interest and the decision to become an entrepreneur. Interest mediates the effect of age, education, gender, experience, and the number of family member on the decision to become an entrepreneur.